Kajian soma dampar dalam konteks peraturan pemerintah kelautan dan perikanan nomor 2 tahun 2015 - Wulan Prily Loth; Lefrand Manoppo; Mariana Elizabeth Kayadoe (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2021)
ABSTRACTIn 2015, the Ministry of Marine Affairs and Fisheries has issued a regulation concerning on several types of fishing equipment. The Regulation of the Minister of Marine Affairs and Fisheries No. 2 of 2015 prohibits the use of trawler fishing equipment (trawls) and pull trawler (seine nets), where Soma Dampar is one of the fishing tools prohibited by the regulation. This research aims to find out the contrary of Soma Dampar operation to the Regulation of the Minister of Marine Affairs and Fisheries No. 2 of 2015, and also to find out the advantages and disadvantages from the use of Soma Dampar fishing equipment. This research was done by following a descriptive method, which is a method of examining the status of a group of people, an object, a set of conditions, a system of thought, or a class of events in the present. The data was retrieved by conducting interviews, and through data with library studies. The result shows that the use of Soma Dampar does not conflict with Regulation of the Minister of Marine Affairs and Fisheries No. 2 of 2015, because the operation of Soma Dampar in North Suawesi, especially in Kelurahan Binuang has more regular procedures of operation. The ecological impact caused is relatively small, and in terms of economic, it is very useful for the life of the fishermen. The government is expected to run a training regarding the use of environmentally-friendly fishing equipment to the community, especially to fishermen; and also to review the Regulation of the Minister of Marine Affairs and Fisheries No. 2 of 2015.ABSTRAK Pada tahun 2015 Kementrian Kelautan dan Perikanan telah mengeluarkan peraturan tentang pelarangan beberapa jenis alat penangkapan ikan yang di keluarkan dalam Peraturan Menteri Kelautan dan perikanan No.2 Tahun 2015 tentang larangan penggunaan alat penangkapan ikan pukat hela (Trawl) dan pukat tarik (Seinen Nets),di mana salah satu alat tangkap yaitu Soma Dampar merupakan salah satu alat tangkap yang di larang oleh peraturan tersebut. Penelitian ini bertujuan untuk mengetahui pengoperasian Soma Dampar bertentangan dengan Permen Kelautan dan Perikanan No.2 Tahun 2015 dan untuk mengetahui baik buruknya penggunaan alat tangkap Soma Dampar. Penelitian ini dikerjakan dengan mengikuti metode deskriptif yang merupakan suatu metode dalam meneliti status sekelompok manusia, suatu objek, suatu set kondisi, suatu sistem pemikiran ataupun suatu kelas peristiwa pada masa sekarang. Pengambilan data dilakukan melalui wawancara dan data dengan studi pustaka. Hasil Penelitian menujukan bahwa penggunaan soma dampar tidak bertentangan bertentangan dengan Permen Kelautan dan Perikanan No. 2 Tahun 2015. Sebab pengoperasian Soma Dampar di Sulawesi Utara khususnya kelurahan Binuang memiliki prosedur atau tata cara pengoperasian yang lebih teratur. Dampak ekologi yang diakibatkan relative kecil, dan dari segi ekonomi sangat memberikanan manfaat bagi kehidupanan masyarakat nelayan. Diharapkan Pemerintah mensosialisasikan pelatihan penggunaan alat tangkap yang ramah lingkungan kepada masyarakat khususnya nelayan dan pengkajian kembali Permen KP. No.02 Tahun 2015.